Coronally advanced flap with and without platelet-rich fibrin in the treatment of multiple adjacent recession defects: A randomized controlled split-mouth trial - Anushree Manohar Potey; Rajashri Abhay Kolte; Abhay Pandurang Kolte; Dhawal Mody; Girish Bodhare; Resham Pakhmode (Wolters Kluwer Medknow Publications, 2019)
Background: The objective of our study was to evaluate and compare the effectiveness of coronally advanced flap (CAF) with or without the use of platelet-rich fibrin (PRF) membrane in the treatment of multiple adjacent recession defects (MARD) clinically and by cone-beam computed tomography (CBCT). Materials and Methods: Twenty healthy patients having 75 MARD were allocated randomly to CAF with orthodontic button group (CAFB) or CAFB + PRF membrane group (CAFB + PRF). Clinical parameters such as gingival recession depth (GRD), probing depth (PD), and keratinized tissue width (KTW) were calculated at baseline, 3 months, and 6 months. The distance from the facial alveolar crest of bone to gingival margin bone and gingival thickness (GT) at three different points were assessed by CBCT at baseline and 6-month postsurgery. Esthetic outcome and postoperative discomfort were evaluated using root coverage esthetic score and visual analog scale, respectively. Results: Percent root coverage achieved in CAFB category was 93.17% ± 13.23% and that in CAFB + PRF group was 95.68% ± 10.13% at 6 months, with no notable difference. Similarly, no difference was found in either group in GRD reduction, PD, and CAL postoperatively. Use of PRF resulted in statistically highly significant (P < 0.001) increased GT at 6 months' time point as compared to participants treated with CAF without PRF, which indicates clinical and esthetic benefits achieved through the procedure. Conclusions: CAFB can be used successfully to treat MARD with predictable outcome. Additional benefit in terms of gain in KTW and GT can be achieved when PRF membrane is used as an adjunct.